The Effect of Macroeconomic Fundamental Factors On Corporate Value Through Financial Performance As Intervening Variables In Manufacturing Companiesn In Indonesia Stock Exchange - Hadi, Isnur; Taufik, Taufik; Herwanto, Deddy (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study aims to determine the effect of macroeconomic fundamental factors on firm value through financial performance as an intervening variable at manufacturing companies in Indonesia Stock Exchange. The data used are panel data, data cross section 54 companies and time series data period from 2011 to 2015. The purpose of sampling method used this research Methods Data collection techniques using purposive sampling 54 companies manufacturing sector BEI 2011-2015. Data collection technique used is purposive sampling method. Methods of data analysis in this study using path analysis (path analysis). The result of analysis shows that; Inflation and interest rates have a significant negative effect on financial performance and firm value while the exchange rate has no effect. Economic growth has a significant positive effect on financial performance and firm value. Financial performance has a significant positive effect on firm value. Inflation and Tribes directly affect the value of the company. Financial performance does not mediate the effects of inflation, interest rates and exchange rates on corporate value. Economic growth has an indirect effect on corporate value through financial performance as an intervening variable.